Elementary school teachers' utilization of local cultural materials in social studies - Abuso, Julian Elloso 1944- (s.n.], 1970)
The objective of the study is to investigate the extent of elementary school teachers' utilization of local cultural materials in Social Studies. It furnished pertinent data on the extent and manner of teachers', curriculum planners', and textbook writers' utilization of local cultural resources.